Pengembangan E-LKPD Berbasis Science, Environment, Technology, and Society (SETS) Untuk Meningkatkan Literasi Sains Siswa - Lutfiatul Fuddah; Ulin Nuha (Universitas Garut, 2026)
Scientific literacy is a fundamental competency in science education, however, the result of the 2022 PISA assessment indicates that the scientific literacy achievement of Indonesian students remains below the expected level, highlighting the need for more contextual and innovative learning approaches. One potential solution is the development of interactive teaching materials in the form of an electronic student worksheet (E-LKPD) based on the Science, Environment, Technology, and Society (SETS) framework, which integrates scientific concepts with environmental issues, technological advancements, and their impacts on society. This study aims to examine the validity, practicality, and effectiveness of the SETS-based E-LKPD in enhancing junior high school students’ scientific literacy. The research employed a research and development (R&D) method using the ADDIE model. The trial participants were seventh-grade students of SMP Negeri 8 Jember, with the research sample drawn from class VII E. Data were collected through expert validation, observations of learning implementation, student response questionnaires, and scientific literacy tests administered as pre-tests and post-tests. The findings demonstrate that the SETS-based E-LKPD is valid (95%), practical (95%), and effective in improving students’ scientific literacy (78%). Therefore, the SETS-based E-LKPD is considered suitable as an alternative instructional material to support the improvement of students’ scientific literacy. Keywords: E-LKPD SETS-based, Science Literacy, Teaching Materials